2015
DOI: 10.3389/fpls.2015.00718
|View full text |Cite
|
Sign up to set email alerts
|

A novel workflow correlating RNA-seq data to Phythophthora infestans resistance levels in wild Solanum species and potato clones

Abstract: Comparative transcriptomics between species can provide valuable understanding of plant-pathogen interactions. Here, we focus on wild Solanum species and potato clones with varying degree of resistance against Phytophthora infestans, which causes the devastating late blight disease in potato. The transcriptomes of three wild Solanum species native to Southern Sweden, Solanum dulcamara, Solanum nigrum, and Solanum physalifolium were compared to three potato clones, Desiree (cv.), SW93-1015 and Sarpo Mira. Desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
1
19
0
1
Order By: Relevance
“…For example, based on sequence identity a candidate of the AtDIR1 protein, which in Arabidopsis functions in the signal transduction of SAR, has been suggested to have a functional homologue in tomato localized in the phloem sap [116]. Frades et al [117] recently used RNA-seq to assembly and compare transcriptomes of three potato clones with three wild relatives of potato in order to find and characterize transcript families correlating with the level of resistance to P. infestans . A similar approach can be used to identify putative IR factors.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…For example, based on sequence identity a candidate of the AtDIR1 protein, which in Arabidopsis functions in the signal transduction of SAR, has been suggested to have a functional homologue in tomato localized in the phloem sap [116]. Frades et al [117] recently used RNA-seq to assembly and compare transcriptomes of three potato clones with three wild relatives of potato in order to find and characterize transcript families correlating with the level of resistance to P. infestans . A similar approach can be used to identify putative IR factors.…”
Section: Induced Resistance Mechanisms In Solanaceaementioning
confidence: 99%
“…To date, over 20 resistance (R-) genes conferring resistance against potato late blight have been cloned, and all belong to the nucleotide-binding, leucinerich-repeat (NLR) class (Jo et al 2015). Many of these R-genes have been successfully transferred into cultivated potato (Frades et al 2015). However, R-gene-mediated resistance (known as qualitative or major resistance) has been rapidly overcome by fast-evolving P. infestans isolates (Khavkin 2015).…”
mentioning
confidence: 99%
“…As complicated as the mechanisms of disease resistance in plants can be, genome-wide expression profiling during pathogen infection can help to identify key components of resistance pathways (Feys and Parker 2000). Although transcriptome dynamics during the interaction between potato and P. infestans have been reported (Gao et al 2013;Ali et al 2014;Frades et al 2015;Yang et al 2018), none of these studies investigated the responses of a single host to different isolates with contrasting infection capabilities. In our previous study, we identified two P. infestans isolates, 90128 and CN152, that resulted in an incompatible and compatible interaction, respectively, on the S. andigena genotype 03112-233 (2n = 4x = 48), which was obtained from the National Research Support Project-6 (NRSP-6) in the United States.…”
mentioning
confidence: 99%
“…Other noteworthy transcripts only identified by differential expression analysis are a Rhicadhesin receptor (DMG400037420), an Erwinia induced protein 2 (DMG400023621) and several members of Zinc knuckle family proteins (DMG400036915, DMG400022758, DMG400028865). Not much is known about their role in resistance, but the Zinc knuckle family has previously been shown to be expanded in Solanum species with high level of P. infestans resistance [17].…”
Section: Identified Trait-associated Transcriptsmentioning
confidence: 99%